2012
DOI: 10.1038/ismej.2012.51
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ammonia-oxidizing archaea and bacteria populations and contributions to soil nitrification potentials

Abstract: It is well known that the ratio of ammonia-oxidizing archaea (AOA) and bacteria (AOB) ranges widely in soils, but no data exist on what might influence this ratio, its dynamism, or how changes in relative abundance influences the potential contributions of AOA and AOB to soil nitrification. By sampling intensively from cropped-to-fallowed and fallowed-to-cropped phases of a 2-year wheat/fallow cycle, and adjacent uncultivated long-term fallowed land over a 15-month period in 2010 and 2011, evidence was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
79
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(95 citation statements)
references
References 29 publications
13
79
2
1
Order By: Relevance
“…This trend is clearly noticeable in QY soils, which is consistent with the previous observations of AOA dominance in a range of soils (He et al 2007;Taylor et al 2012). Moreover, the higher ratio of AOA to AOB in acid QY soils as compared to other non-acidic soils further confirmed the dominant role of AOA in acid soil habitats (He et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…This trend is clearly noticeable in QY soils, which is consistent with the previous observations of AOA dominance in a range of soils (He et al 2007;Taylor et al 2012). Moreover, the higher ratio of AOA to AOB in acid QY soils as compared to other non-acidic soils further confirmed the dominant role of AOA in acid soil habitats (He et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…3a), which was in agreement with previous studies in a large number of agricultural soils (Wu et al 2011;Habteselassie et al 2013;Chen et al 2015). It has been reported that AOB growth is favored by high-N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected (Di et al 2009(Di et al , 2010a. The stronger suppression of the AOB population size by C 2 H 2 than DCD was observed, suggesting a coincidence of dynamics between the AOB population and N 2 O emission.…”
Section: Nitrosospira Nitrososmonassupporting
confidence: 92%
“…AOA did not respond to the application of NH 4 + in the alluvial soil, while it was inhibited with respect to the control in the red soil, thus confirming what it was obtained in agricultural soils (Wu et al 2011;Ai et al 2013;Habteselassie et al 2013;Di et al 2014Di et al , 2014Chen et al 2015). Generally, AOB growth is favored by high NH 4 + -N soil conditions (Jia and Conrad 2009;Verhamme et al 2011;Taylor et al 2012), whereas AOA growth is not affected or suppressed (Di et al 2009(Di et al , 2010Di and Cameron 2011;Di et al 2014). Actually, the AOA population only grew in the control in the red soil, where NH 4 + was generated from mineralised organic N, suggesting that AOA growth is favored in low fertility status soils (Nicol et al 2008;Di et al 2009Di et al , 2010Zhang et al 2012).…”
Section: Discussionsupporting
confidence: 72%